2020
DOI: 10.1002/agj2.20065
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield, and nitrogen uptake and translocation of peanut under different nitrogen management systems in a wheat–peanut rotation

Abstract: Better N fertilizer management is essential for improving crop productivity and reducing N losses to the environment. However, few studies have reported N absorption, use, and balance in a wheat (Triticum aestivum L.)-peanut (Arachis hypogaea L.) relay intercropping system. This study aimed to determine the effects of different N application rates and ratios at different maturation stages on the yield and N use of peanut in this system. Nitrogen (300 kg ha −1 ) was applied the day before sowing and at jointing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The row spacing was >0.45 m, and the plant spacing was >0.30 m. An isolation zone was set up between the test plots to avoid the mass transfer between plots. Reasonable application of nitrogen fertilizer is of great significance for the growth of peanuts because the amount of nitrogen required will vary greatly with the different planting methods, planting conditions, and variety yield, the problem of nitrogen fertilizer amount for peanuts has been a concern to scholar for a long time ( 24 , 25 ). According to different nitrogen rates of biogas slurry, the experimental plots were divided into five groups, including no fertilization, low application rate [8.5 g total nitrogen (TN)/m 2 ·year], European Union application standard (17 g TN/m 2 ·year), domestic average application rate (34 g TN/m 2 ·year) ( 26 ), and excessive application (68 g TN/m 2 ·year).…”
Section: Methodsmentioning
confidence: 99%
“…The row spacing was >0.45 m, and the plant spacing was >0.30 m. An isolation zone was set up between the test plots to avoid the mass transfer between plots. Reasonable application of nitrogen fertilizer is of great significance for the growth of peanuts because the amount of nitrogen required will vary greatly with the different planting methods, planting conditions, and variety yield, the problem of nitrogen fertilizer amount for peanuts has been a concern to scholar for a long time ( 24 , 25 ). According to different nitrogen rates of biogas slurry, the experimental plots were divided into five groups, including no fertilization, low application rate [8.5 g total nitrogen (TN)/m 2 ·year], European Union application standard (17 g TN/m 2 ·year), domestic average application rate (34 g TN/m 2 ·year) ( 26 ), and excessive application (68 g TN/m 2 ·year).…”
Section: Methodsmentioning
confidence: 99%
“…Intercropping is a sustainable and intensive cropping pattern that has the advantages of improving crop yields ( Liu et al., 2020 ; Zou et al., 2021 ) and land use efficiency ( Yu et al., 2015 ; Feng et al., 2021 ), inhibiting weeds, and reducing pests and diseases ( Brooker et al., 2015 ; Beillouin et al., 2021 ; Chadfield et al., 2022 ). Many previous studies have confirmed that intercropping of gramineous and leguminous crops has yield advantages, for instance, intercropping of maize and soybean, maize and peanut ( Li et al., 2019 ), and sorghum and soybean ( Wang et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has demonstrated that nitrogen fertilization applied 10 weeks after planting had minimal effects on the shoot and root-rhizome biomass [13]. Liu, Gao, Li, et al [14] reported that the peanut pod yield increased within a certain range of nitrogen application; the yield no longer increased or even declined beyond the optimal nitrogen application rate [15]. Therefore, the impacts of nitrogen supply and utilization vary under different ecological environments.…”
Section: Introductionmentioning
confidence: 99%